Immune reconstitution of human cytomegalovirus-specific T lymphocytes after allogeneic hematopoietic stem cell transplantation and their predictive role in reactivation - Zhao, Yuanqi; Zhen, Sisi; Wang, Jiali; Wang, Jieru; Ma, Runzhi; Liu, Li; Pang, Aiming; Zhang, Rongli; Chen, Xin; Zhai, Weihua; Yang, Donglin; He, Yi; et al. (Frontiers in Immunology, 2025)
Human cytomegalovirus (HCMV) is the most common virus to affect the recipients of allogeneic hematopoietic stem cell transplantation (allo-HSCT). HCMV reactivation increases the risk of secondary fungal and bacterial infections, as well as that of non-relapse mortality after allo-HSCT. This study investigates the post-transplantation reconstitution of HCMV-specific T cells and their role in the regulation of HCMV infections. Peripheral blood samples from CMV-seropositive allo-HSCT recipients (R+) and CMV-seropositive donors (D+) were collected from October 2019 to June 2021. Continuous quantification and function monitoring of CMV-specific CD4+/CD8+T lymphocytes were performed by flow cytometry after stimulation in an HCMV-pp65 pool in vitro and intracellular cytokine staining was performed. Plasma CMV–DNA was quantitatively detected by qPCR. The median age of patients (n = 131) was 34 (23–45) years. Post-transplantation HCMV reactivation occurred in 88 (67.2%) patients. HCMV-responsive CD4+T cells in non-HCMV reactivation patients was significantly higher than that in HCMV reactivation patients 30 days after transplantation (0.21 cells/μL vs 0.10 cells/μL; P = 0.005). Kaplan–Meier analysis showed that the incidence of HCMV reactivation in patients with low levels of HCMV-responsive CD4+T cells (<0.14 cells/μL) was significantly higher than that in patients with high levels of HCMV-responsive CD4+T cells (>0.14 cells/μL) (83.9% vs 54.7%; P < 0.001). Patients lacking HCMV-responsive CD8+T cells (<2 cells/μL) 60 days after allo-HSCT had a significantly higher risk of HCMV reactivation 100 days after transplantation (HR 9.932; P = 0.005). Patient age and the mononuclear cell-infusion level were correlated with the reconstructive levels of HCMV-responsive CD8+T cells 60 days after transplantation. Poor recovery of HCMV-responsive CD4+T cells 30 days post-transplantation is closely related to the risk of HCMV reactivation. The level of HCMV-responsive CD8+T cells 60 days post-transplantation is a good predictor for late-onset HCMV reactivation, which is particularly important for outpatient monitoring and management of patients with allo-HSCT, and facilitates individualized risk stratification for HCMV reactivation.